Antifungal Activity of Polyalthia longifolia (Sonn.) Thw. against Seed Borne Fungi of Paddy (Oryza sativa. L). - Raveesha. K.A3, Lalitha. V1,3*, Kiran. B2,3 and (Journal of Phytology, 2011)
Antifungal activity of aqueous (10-50% concentration) and solvent extract (500µl and 1000µl concentration) of Polyalthia longifolia were tested against ten seed borne fungi of paddy (Oryza sativa. L) in vitro condition. In aqueous extract, A. alternata recorded a maximum inhibition of 92.88% followed by F. solani (87.10%), F. moniliforme (86.40%), D. halodes (86.07%), F. oxysporum (85.14%), C. lunata (83.33%) and D. tetramera (83.02%) at 50% concentration compared to synthetic fungicide, Dithane M-45, Captan, Benlate, Thiram and Bavistin at 2% recommended dosage. In solvent extract petroleum ether extract recorded a complete and maximum inhibition in all the test fungi at 1000 µl concentration. Petroleum ether is followed by Benzene, ethanol, Methanol and Chloroform.